Expectativas reprodutivas de pais e filhos: uma avaliação do conflito pais-prole - Menezes, Luilia Suelly Cruz (2015)
Reproduction is an essential part of humans species’ existence and survival. We are interested in securing it, and having a direct interest in the reproduction of those with whom we have strong genetic relationship. Trivers (1974) featured the parent-offspring conflict, as a divergence about the parents’ investment, which has been mainly studied in the early stages of children’s development. However, the divergence in investment can also be expressed at the time of the reproductive decisions of the offspring. Thus, we investigated whether parents and children have conflicting interests regarding reproductive expectations of the children, understanding reproductive expectations as desired age to marry, have children, have sexual intercourse and desired amount of children. We found that parents and children disagree on some of these points, we also find a more conservative expectation when it comes to daughters, reiterating the daughter-guarding hypothesis. When we consider how much help would be given towards the up bringing of a grandson, we found a clear variation according to the age of the baby's parents: the younger the baby’s parents are, the larger the amount of assistance would be provided by grandparents. Considering the amount and quality of offspring and conditions of reproduction, parental investment is an element that presents itself closely linked to the history of the subject's life. Parents are the first to communicate to children how the environment in which they are inserted is presenting itself. As the life history is closely linked with reproduction, and, therefore, with parental investment, we intend to investigate whether there is a correlation between aspects of the individuals’ history of life (unpredictability and parental care) and their reproductive expectations, seeking further assess on whether there is relationship between parents' life history and their reproductive expectations for their children. We find evidence that partially confirm our expectations; we find relationships of some elements of reproductive expectations with indicators of unpredictability and parental care. The experiences of parents also reflected in their expectations for their children, with a more present correlation to their expectations for daughters. From our results, we find evidence that parent-offspring conflict appears in the reproductive expectations of children and relates to aspects of individuals’ life history.